Emerging role of non-coding RNA in neural plasticity, cognitive function, and neuropsychiatric disorders - Spadaro, Paola; Bredy, Timothy W. (Frontiers in Genetics, 2012)
Non-coding RNAs have emerged as critical regulators of transcription, epigenetic processes, and gene silencing, which make them ideal candidates for insight into molecular evolution and a better understanding of the molecular pathways of neuropsychiatric disease. Here we provide an overview of the current state of knowledge regarding various classes of ncRNAs and their role in neural plasticity and cognitive function, and highlight the potential contribution they may make to the development of a variety of neuropsychiatric disorders, including schizophrenia, addiction and fear-related anxiety disorders.